Pengembangan E-Modul Praktikum Crocodile Physics Berbasis POE - Dwi Putri Natalia; Monica Merry Febriyana; Refa Tri Ustati; Yulika Rahmawati (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Practically is one way to understand the concept of physics. However, situation of  pandemic COVID-19 make practical work in laboratory unable to implemented. Therefore, use of virtual laboratory is one way to solve this problem. Crocodile Physics is one of the best programs that can use. But this program is not yet well known and has some of obstacles to be operated by teachers and students in Indonesia. So, it takes a media of learning to be a guide in the operation of the program. This study aims to test the feasibility of “E-Lab Module Crocodile Physics-Based POE”. This research uses qualitative research method with R & D (Research and Development) developed by researchers is model 4-D until the stage of development. E-Lab Module is also said to be feasible based on validation of material experts, media experts, and linguists, with an average total score of 90,77% by assessment of the validation of material experts, the average total score amounted to 78.12 % by assessment of the validation of media experts, and the average total score of 83,33% by assessment of validation of language experts, each the result entered on the criteria of “worth”.